PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DI HOTEL CANGGU DREAM VILLAGE - Manika Dewi, Anak Agung Candra; Sihombing, Irene Hanna H.; Pratiwi, Kadek Andita Dwi (JURNAL BISNIS HOSPITALITI, 2023)
The importance of the existence of human resources in the development of tourism services Business, as can be seen from the ability of a company to develop, is very dependent on the ability of employees to carry out work tasks that are directed to the development of the company. The purpose of this study was to analyze the effect of leadership style on employee performance at Canggu Dream Village Hotel. The number of samples used was 45, using the saturated sample method. Data collection using Likert scale questionnaire Data analysis techniques using simple linear regression analysis Hypothesis testing is done using the t-test. The results showed that the democratic leadership style variable was 6.626 compared to the t table, namely 1.6, which means rejecting H0 or H1 was accepted because t-count> t-table = 6.626> 1.6, meaning that democratic leadership style has a significant positive effect on employee performance at the Canggu Dream Village Hotel. Thus, it can be interpreted that the better the application of democratic leadership style, the higher employee performance. The magnitude of the influence of democratic leadership style on employee performance is 49.4%. It is expected that leaders provide time or opportunities for subordinates to convey input.